Probabilistic performance analysis of existing buildings under earthquake loading - Xavier Romão (2012)
A probabilistic methodology is proposed for the seismic performance analysis of existing buildingsusing global metrics to determine if the behavior conforms to a given limit state. The referred performancemetrics are the mean annual frequency of the limit state, the corresponding expected lossassociated to the repair of the building, and the corresponding number and type of mechanisms thatoccur. The consideration of these assessment parameters to control building performance widensthe scope of the limit state definitions proposed in current codes. Therefore, current limit statedescriptions were updated to establish adequate risk- and cost-related limit state definitions usingthe Eurocode 8 Part 3 proposals as a basis for discussion. The description of the proposed procedureis detailed and addresses its applicability for different limit states and its ability to include the uncertaintyin the limit state capacities. An application involving the performance analysis of a reinforcedconcrete structure for several limit states is also presented and discussed.